2009
DOI: 10.1186/1471-2458-9-158
|View full text |Cite
|
Sign up to set email alerts
|

Journeys to tuberculosis treatment: a qualitative study of patients, families and communities in Jogjakarta, Indonesia

Abstract: Background: Many tuberculosis (TB) patients in Indonesia are diagnosed late. We seek to document patient journeys toward TB diagnosis and treatment and factors that influence health care seeking behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
41
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 8 publications
9
41
0
2
Order By: Relevance
“…Uplekar et al found that in the Pune city, 60% of individuals with chest symptoms first approached a private provider and in another study by the same author, it was found to be 86%. 14,15 Present finding is consistent with other studies by Kelkar-Khambete A et al at Pune 83% and Nair N et al in the SEAR 60-70% and Rintiswati N et al [16][17][18] However, studies from South Sudan and Hong Kong reported lower figures of 17% and 42.6% respectively. Accessibility was found to be the main reason for approaching the health facility.…”
Section: Discussionsupporting
confidence: 81%
“…Uplekar et al found that in the Pune city, 60% of individuals with chest symptoms first approached a private provider and in another study by the same author, it was found to be 86%. 14,15 Present finding is consistent with other studies by Kelkar-Khambete A et al at Pune 83% and Nair N et al in the SEAR 60-70% and Rintiswati N et al [16][17][18] However, studies from South Sudan and Hong Kong reported lower figures of 17% and 42.6% respectively. Accessibility was found to be the main reason for approaching the health facility.…”
Section: Discussionsupporting
confidence: 81%
“…The performance of the health services regarding dialogue with the families of TB patients about the disease and treatment was unsatisfactory for the study subjects, which corroborates the results of investigations carried out in São José do Rio Preto-SP (8) and Jogjakarta, Indonesia (19) . Consequently, health professionals should acknowledge the role of the families in relation to the sick family member.…”
Section: Discussionsupporting
confidence: 73%
“…It is important to use accessible language to thoroughly explain the types and effects of drugs, the duration, benefits and adverse reactions of treatment, and the consequences of abandoning treatment (16) . As found in this study, other investigations revealed that patients must distance themselves from their family members when eating, sleeping or cooking to prevent transmission (19)(20) . This distancing makes patients less prone to share their problems and concerns with family members and less motivated to continue the treatment (14) .…”
Section: Discussionmentioning
confidence: 82%
“…TB sufferers who had been receiving care at healthcare facilities showed inactive TB bacilli that would not lead to transmission (negative MTB bacilli status) after two weeks' treatment of active TB bacilli (positive MTB bacilli status) (4,5). Yet this TB condition, also known as TB conversion, was rarely being evaluated (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%